Point cloud processing and toolpath generation for robotic 3D printing - Goh, Zhi Yong (Nanyang Technological University, 2023)
Additive manufacturing (AM) or 3D printing is a manufacturing technique of producing a part later-by-layer to obtain a model of a specific geometrical and mechanical specifications. AM provides a lot of benefits as compared to traditional manufacturing as it allows fast prototyping and customization of precise metal or alloy parts with difficult shapes. Traditionally, 3D printing of a part requires stereolithography tessellation language (STL) type files which requires computer aided design software like SolidWorks or Fusion 360 to create a drawing to be sliced and 3d printed. There is ongoing research on the “scan and plan” (SNP) method where a laser scanner will be utilized to generate point cloud data which will be fed to a software, which can be used to generate toolpaths for the robot arm or joints to print the part, which skips the need for STL file. Literature review on the “scan and plan” technique will be explored and discussed to obtain insights and knowledge from previous studies. In this report the emphasis is on exploring software applications that use the Robotics Operating System (ROS) programming language in generating an optimized tool path from a laser scanned point cloud of a part for an AM task.